The Psychopathology Changes in non-Obese PCOS Women Do Not Show any Influence on Neuropeptide Y Level - Mariza Yustina (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To compare the Neuropeptide Y (NPY) levels in nonobese Polycystic Ovary Syndrome (PCOS) patients without insulin resistance and non-obese women without insulin resistance, in consideration of the psychopathologic conditions occurring in PCOS patients as well as the influence of these changes in affecting NPY levels. Methods: The subject was fourteen PCOS patients and 20 non-obese normal women, both without insulin resistance. The measurements of blood NPY levels using the ELISA method and a psychology assessment using Symptom Check List 90 (SCL-90) were carried out. Statistical analysis was performed using SPSS 17. Results: From 20 PCOS patients included in this study, 6 subjects (30%) were detected as having psychopathologic problems through completion of the SCL-90 questionnaire, with a cut-off score of >70 points. Measurement of NPY levels using ELISA found a mean NPY level of 8.02 Â± 3.92 (95% CI 2.39 - 18.66) in the PCOS group compared to a mean of 7.78 Â± 4.31 pg/ml (95% CI 0.74 - 15.47) in the control group. No significant difference was found in the mean levels of NPY between the two groups. Statistical assessment using the Spearman 2-variable correlation test also found no significant correlation between NPY levels and the SCL-90, scores in the PCOS group. Conclusion: There was no significant difference in NPY levels between the PCOS group and control group. Thirty percent of non-obese PCOS patients without insulin resistance were identified as having psychopathologic conditions. But in this group of patients, the psychopathologic changes had no influence on the levels of blood NPY. [Indones J Obstet Gynecol 2012; 36-3: 125-9] Keywords: neuropeptide Y, PCOS, psychopathologic conditions